A Novel Model for Advancing Sexual Assault Education and Prevention on Campus. (October 2019) - Cavanaugh, Courtenay E.
Teachers of psychology have been called to both educate college students about interpersonal violence (e.g., sexual assault) and use service learning. However, few models exist for how teachers may simultaneously address both of these calls. This article describes a service-learning course in psychology that integrated an evidence-based, bystander intervention program (BIP) into it in order to provide students with both sexual assault education and roles for advancing sexual assault prevention on campus. Sixteen students in an undergraduate psychology course watched TakeCare, a video shown to improve students' positive bystander behavior to prevent sexual assault and then facilitated delivery of TakeCare to 156 other students on campus. This course illustrates a novel model for advancing sexual assault education and prevention on campus, and the model may be used in other psychology courses. Future directions for implementing and evaluating this model are described.